Diffusion bonding of fine grained high carbon steels in the super-plasticity temperature range - Taskin, Mustafa; Orhan, Nuri; Ozan, Sermin (Natl Inst Science Communication, 2006)
In this Study, diffusion bonding behaviour of two high carbon hypoeutectoid steels was investigated. The steel specimens were heat treated to induce a fine grain structure and diffusion bonded within a temperature range where these steels exhibit superplasticity. The results showed that these Steels Could be bonded successfully at 650 degrees C and 735 degrees C within the superplastic temperature range, but poor diffusion bonds were fabricated at a temperature of 850 degrees C. The poor bonding was attributed to an increase in grain size, which not only reduce grain boundary diffusion mechanisms, but also a loss in superplastic deformation behaviour could be expected.
Keywords: Stainless-Steel; Theoretical-Model; Superplasticity; Alloys